2020 Update of the quality indicators for acute myocardial infarction: a position paper of the Association for Acute Cardiovascular Care: the study group for quality indicators from the ACVC and the NSTE-ACS guideline group. Issue 2 (7th February 2021) - Schiele, François; Aktaa, Suleman; Rossello, Xavier; Ahrens, Ingo; Claeys, Marc J; Collet, Jean-Philippe; Fox, Keith A A; Gale, Chris P; Huber, Kurt; Iakobishvili, Zaza; Keys, Alan; Lambrinou, Ekaterini; et al.
Abstract: Aims: Quality indicators (QIs) are tools to improve the delivery of evidence-base medicine. In 2017, the European Society of Cardiology (ESC) Association for Acute Cardiovascular Care (ACVC) developed a set of QIs for acute myocardial infarction (AMI), which have been evaluated at national and international levels and across different populations. However, an update of these QIs is needed in light of the accumulated experience and the changes in the supporting evidence. Methods and results: The ESC methodology for the QI development was used to update the 2017 ACVC QIs. We identified key domains of AMI care, conducted a literature review, developed a list of candidate QIs, and used a modified Delphi method to select the final set of indicators. The same seven domains of AMI care identified by the 2017 Study Group were retained for this update. For each domain, main and secondary QIs were developed reflecting the essential and complementary aspects of care, respectively. Overall, 26 QIs are proposed in this document, compared to 20 in the 2017 set. New QIs are proposed in this document (e.g. the centre use of high-sensitivity troponin), some were retained or modified (e.g. the in-hospital risk assessment), and others were retired in accordance with the changes in evidence [e.g. the proportion of patients with non-ST segment elevation myocardial infarction (NSTEMI) treated with fondaparinux] and the feasibility assessments (e.g. the proportion of patients with NSTEMI whom risk assessment is performed using the GRACE and CRUSADE risk scores). Conclusion: Updated QIs for the management of AMI were developed according to contemporary knowledge and accumulated experience. These QIs may be applied to evaluate and improve the quality of AMI care.